Factors of product competitiveness of industrial enterprises - Ukubassova, G.S.; Amirbekova, A.B. (BUKETOV BUSINESS REVIEW, 2019)
Increasing the efficiency of production of the enterprise is the most important task of the modern stage of economic development. Developing the competitiveness of products plays a huge role in its solution. As a rule, this implies a complete or partial renewal of the range, restructuring of the organizational structure, technical re-equipment of production, improvement of its financial indicators to achieve the set development goals, as well as introduction of fundamentally new management methods. Both the strategy developed and the specialized programs, which are based on the achievement of certain financial indicators, can provide a source of improvement in financial indicators. In particular, it can be both a constant guarantee of profit, as well as an increase and optimization of internal processes, which are considered the basis of sustainable operation of the enterprise. Consideration of what can be considered competitive industrial products and determine the relevance of the study. The novelty of the proposed methodology is determined by the fact that the basis of competitiveness is considered not only a certain strategy in the achievement of planned indicators, but also a strategy for the formation of an internal stable environment of the enterprise, which can be implemented taking into account the needs of production and its potential development. The implementation of the enhancement of internal sustainability is expected to be carried out on the basis of an evaluation of the external cooperation system. The practical significance of the work is determined by the need to form a certain relationship between internal stability and the possibilities of external change.